(untitled) - Kikuchi- Kan (Japan, 1961)
This novel is a compelling story of a Buddhist monk who undertakes a seemingly impossible task in order to fulfill his spiritual purpose to help those he had previously harmed. It shows how, in the process of converting his karma, he also transforms the lives of others. It is based on the life of an actual monk who lived during the 18th century in Japan and shows that no matter what a person has done, including murder and robbery, he can completely turn his life around and know the greatest fulfillment---the direct experience of the Eternal, the Buddha Nature---and can then commit his life to selfless service because it is his nature to do so.
Keywords: Vago, Kimiko